Do IPOs Affect the Prices of Other Stocks? Evidence from Emerging Markets - Braun, Matías; Larrain, Borja (Review of Financial Studies, 2009)
We show that the introduction of a large asset permanently affects the prices of existing assets in a market. Using data from 254 initial public offerings (IPOs) in 22 emerging markets, we find that portfolios that covary highly with the IPO experience a decline in prices relative to other portfolios during the month of the issue. The effects are stronger when the IPO is issued in a market that is less integrated internationally and when the IPO is bigger. This evidence is consistent with the idea that shocks to asset supply have a significant effect on asset prices.